The right of people with disabilities to employment - Amjad Mohammed Hussein Al-AWLAQI; Amal Mohamed Shalaby Khadragey (International Journal of Law Research and Studies, 2025)
This study examines the right of people with disabilities to employment, highlighting its significance and profound impact on their lives. Employment empowers individuals with disabilities to achieve independence from their families, rely on themselves, and enhance their integration into society. Furthermore, it provides them opportunities to contribute to community development and nation-building, fostering a sense of belonging and tangible influence within society. Islamic law, international conventions, and national legislation have reinforced the importance of this right by shedding light on its significance. The Saudi legislator has played a pioneering and distinguished role in addressing the issue of employing persons with disabilities. The study indicates a disparity between legal provisions and practical implementation. Despite the numerous obstacles hindering the employment of people with disabilities, overcoming them remains achievable.